Hare (a photographic technique) - Ballón Aguirre, Enrique (1988)
Of the thousand and one questions that can be addressed to the conditions of production of that phenomenon or "data" called photography, the plenary semiotics chooses only this one: what does it mean and what does a photograph mean?Once the question has been asked, attempting to answer it has supposed to pose previously a new object of knowledge that, in the first place, relocates the general problematic of the photographic meaning, moving it towards an unpublished point of view: that of the intentionality and the motivation of the enunciator that produces it. to relate the sensitive qualities of a particular visual signifier, the frame (level of expression of the photograph) and certain intelligible or meaningful qualities that make it possible to perceive it.